APPLICATION OF AN EXPERT SYSTEM TO IMPROVE CARDIOVASCULAR RISK IN THE WORKPLACE. (June 2018) - Ruilope, L.M.; Quevedo-Aguado, L.; Fernández-Labandera, C.; Martínez-Muñoz, P.; Catalina-Romero, C.; Fernández-Meseguer, A.; Sánchez-Chaparro, M.-Á.; Valdivielso-Felices, P.; Calvo-Bonacho, E.
Abstract : Objective: The aim of this study was to design, develop and test an expert system to help professionals in clinical decision-making as providing an assessment of the health of workers at very high CVR. Design and method: lt was designed and developed an operational web-expert system in ASP Ianguage, which gathers information on risk factors and returns an output with recommendations for management of risk factors based on the 2012 European Guidelines on Cardiovascular Disease Prevention criteria. In the case of needing an intervention or modification of drug treatment, the expert system helps to plan them. The CVR was stratified by the European SCORE system for low-risk countries. A test was conducted with a pilot program providing workers with very high CVR (SCORE >  = 10). The adherence to the Mediterranean diet was assessed by a 14-item questionnaire and physical activity by the International Physical Activity Questionnaire (IPAQ). Results: This pilot study included 148 patients (mean age: 64.5 ± 8.3 years). All the participants were men, 73.6% and 55.2% had hypertension and dyslipidaemia, but only 50.7% and 34.3% of them were receiving anti-hypertensive treatment and lipid-lowering therapy at baseline, respectively. The participants were mostly manual workers (63.5%). 91.8% of them knew they had cardiovascular risk factors. 73.0% were smokers, of which 34.3% expressed their intention to give up smoking in the coming months. The mean BMI was 28.5 kg/m2 and the mean waist circumference was 100.5 cm. After 1-year follow-up, the percentage of patients who met the therapeutic objective for total cholesterol levels (<175 mg/dl) significantly increased (p = 0.03). The percentage of subjects with moderate-to-high adherence to the Mediterranean diet increased form 77.0% to 88.7% (p < 0.001). The percentage of subjects with sufficient-to-high physical activity also increased but not significantly (p = 0.547). Conclusions: Our preliminary results suggest that there is a high potential for improvement in Iifestyle and CVR control among patients at very high cardiovascular risk. The availability of an expert system could facilitate decision-making when providing medical advice. An expert system could be a value-added service in order to standardize health care and to promote the best clinical practice